Evolving strategies to reduce colectomy rates in primary sclerosing cholangitis-inflammatory bowel disease: clinical remission of corticosteroid refractory colitis post-liver transplant with vedolizumab. Issue 4 (5th August 2016) - Mumtaz, Saqib; Goh, Jason; Hirschfield, Gideon M; Ferguson, James; Cooper, Sheldon C
Abstract : Primary sclerosing cholangitis (PSC) is associated with inflammatory bowel disease (IBD) in approximately 70% of patients, with ulcerative colitis (UC) being the most common subtype of IBD identified. There is a paucity of data on the optimum management strategy for IBD flares in the post-liver transplant patient, particularly when refractory to conventional treatments. Vedolizumab is a novel gut-specific monoclonal antibody, which has recently been approved for use by National Institute for Health and Care Excellence for moderate-to-severe UC. We present an exemplar case of successful use of vedolizumab in the management of corticosteroid refractory PSC-IBD after liver transplantation.